Metal nanoparticles enhanced thermophysical properties of phase change material for thermal energy storage. (2020) - Gupta, Neeraj; Kumar, Amit; Dhawan, S.K.; Dhasmana, Hrishikesh; Kumar, Avshish; Kumar, Vivek; Verma, Abhishek; Jain, V.K.
Abstract: Phase change materials (PCMs) are one of the promising materials in thermal energy storage systems. In this work PCM nanocomposites were prepared using melt-blending technique by dispersing metal nanoparticles (Fe, Cu) at mass fraction of 0.5 wt% in magnesium nitrate hexahydrate (MNH), an inorganic salt hydrate PCM. The as-prepared PCM nanocomposites were analyzed by scanning electron microscopy (SEM) and X-ray diffractometer (XRD). Fourier transform infrared spectroscopy (FTIR) analysis was carried out to monitor the changes in chemical nature of PCM nanocomposites. The heat transfer characteristics were investigated by conventional heating system, which were used to carry out melting (charging) and solidification (discharging) cycle of MNH-metal nanocomposites. The experiment results clearly indicates that the rate of melting and solidification of MNH-metal nanocomposites increased at 0.5 wt% mass fraction of metal nanoparticles as compared to MNH. The thermal conductivity of MNH-metal nanocomposites at 0.5 wt% mass fraction of metal nanoparticles (Fe, Cu) in solid phase was measured using the transient hot method, which clearly indicates that thermal conductivity improved to (0.61) W m −1 K −1 for MNH-Fe nanocomposite & (0.63) W m −1 K −1 for MNH-Cu nanocomposite than that of pure MNH (0.4) W m −1 K −1 . The prepared nanocomposites showed good heat transfer characteristics and better thermal conductivity. Therefore, this study demonstrates that metal nanoparticles, added to inorganic PCM (MNH) had a significant potential for enhancing the thermophysical properties and makes it promising candidate for thermal energy application.